Rintisan Green House Sebagai Upaya Peningkatan Ketahanan Pangan Keluarga Desa Putat Lor Kecamatan Gondang Legi - Nanik Ulfa; Mojibur Rohman; Salim Salim; Ecky Zaskia Nurin Farrynda; Alvin Maulana A; Sujoko Sujoko (I-Com: Indonesian Community Journal, 2024)
Putat Lor Village, Gondang Legi District is part of Malang Regency. Gondang Legi District has several programs, one of which is the Sustainable Food Home Area (KRPL) program. To support this KRPL program and based on the evaluation results, the service team carried out a Green House pilot program to make it easier for the community to continue the KRPL program that had been initiated previously. This service program is carried out over a period of 35 days with observation, socialization, training, and evaluation and control activities. In implementing this program, the service team involves residents directly, so that the training process can run effectively and efficiently. Furthermore, after the training was carried out, community members became more aware of how to seed and care for vegetables, so that residents' enthusiasm for implementing KRPL increased.